2020
DOI: 10.1111/den.13644
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pressure study integrated system reflects gastroesophageal junction competence in patients with erosive esophagitis and Barrett´s esophagus

Abstract: Objectives The endoscopic pressure study integrated system (EPSIS) is a novel diagnostic tool for gastroesophageal reflux disease (GERD) by monitoring intragastric pressure (IGP). Evaluation of the lower esophageal sphincter (LES) function may be achieved endoscopically by utilizing this newly developed diagnostic tool. This study aimed to evaluate the association between EPSIS results and gastroesophageal reflux‐related diseases, e.g., erosive esophagitis (EE) and Barrett’s esophagus (BE). Methods This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…T HE PERFORMANCE OF EPSIS has been previously investigated in a pilot study. 5,6 Our group reported that a flat waveform pattern of IGP and an IGP max under 18.7 mmHg could distinguish acid reflux from disorders with similar symptoms with good accuracy. 5 In order to enhance the accuracy and reproducibility of this diagnostic system, the waveform of IGP was characterized in detail by obtaining objective parameters, rather than applying uphill or flat pattern criteria, which can sometimes be subjective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T HE PERFORMANCE OF EPSIS has been previously investigated in a pilot study. 5,6 Our group reported that a flat waveform pattern of IGP and an IGP max under 18.7 mmHg could distinguish acid reflux from disorders with similar symptoms with good accuracy. 5 In order to enhance the accuracy and reproducibility of this diagnostic system, the waveform of IGP was characterized in detail by obtaining objective parameters, rather than applying uphill or flat pattern criteria, which can sometimes be subjective.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were age <18 years, pregnancy, or history of upper gastrointestinal surgery or enrollment in prior EPSIS studies at our institution. 5,6 All study participants underwent EGD, EPSIS, and MII-pH. In selected cases, histopathologic assessment and highresolution manometry were performed to rule out eosinophilic esophagitis and major motility disorders at the discretion of endoscopists.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous reports showed that low maximum IGP and flat pattern are significant predictors of gastroesophageal reflux disease (GERD) 1 . Furthermore, EPSIS correlated with erosive esophagitis and Barrett’s esophagus 2 . As such, EPSIS can be used for the diagnosis of acid reflux during initial upper endoscopy assessment.…”
Section: Introductionmentioning
confidence: 98%
“…1 Furthermore, EPSIS correlated with erosive esophagitis and Barrett's esophagus. 2 As such, EPSIS can be used for the diagnosis of acid reflux during initial upper endoscopy assessment. It is a safe tool that requires only CO 2 insufflation for a short period of time.…”
Section: Introductionmentioning
confidence: 99%